Co-fermentation of Propionibacterium freudenreichii and Lactobacillus brevis in Wheat Bran for in situ Production of Vitamin B12 - Xie, Chong; Coda, Rossana; Chamlagain, Bhawani; Varmanen, Pekka; Piironen, Vieno; Katina, Kati (Frontiers in Microbiology, 2019)
The present study investigated the effect of co-fermentation on vitamin B12 content and microbiological composition of wheat bran. Propionibacterium freudenreichii DSM 20271 was used as the producer of vitamin while Lactobacillus brevis ATCC 14869 was selected to ensure the microbial safety of the bran dough. Fermentation trials were conducted in bioreactors to monitor and adjust the pH of the ferments. Vitamin B12 level reached 357 ± 8 ng/g dry weight (dw) after one day of pH-controlled fermentation with P. freudenreichii monoculture and remained stable thereafter. In co-fermentation with L. brevis, slightly less vitamin B12 (255 ± 31 ng/g dw) was produced in one day and an effective inhibition of the growth of total Enterobacteriaceae and Bacillus cereus was obtained. On day 3, vitamin B12 content in pH-controlled co-fermentation increased to 332 ± 44 ng/g dw. On the other hand, without a pH control, co-fermentation resulted in a stronger inhibition of Enterobacteriaceae and B. cereus but a lower level of vitamin B12 (183 ± 5 ng/g dw on day 3). These results demonstrated that wheat bran fermented by P. freudenreichii and L. brevis can be a promising way to produce vitamin B12 fortified plant-origin food ingredients, which could reduce cereal waste streams and contribute to a more resilient food chain.